THE IMPACT OF BODY-ORIENTED THERAPY ON DEPRESSIVE DRUG USERS - Sadova, Myroslava (PSYCHOLOGICAL JOURNAL, 2020)
We have summarized in our article the empirical and applied results of the studies on the scientific problem of body-oriented therapy and presented its use for drug addicted clients in depressive states. According to the obtained experimental results, the generalized characteristics of the incoming control of depressive state indicators obtained from the used psychodiagnostic tests showed that drug addicted clients’ depressed mood was at high (80-85%) or high-medium (75% ) levels for the majority of tested scales. Three main symptoms of depression were manifested by tests the most clearly: the gastrointestinal somatic symptoms, mental anxiety, working performance and activity. Such results can be justified by the fact that withdrawal from drugs in rehabilitation centres worsen clients’ mood, as their body is accustomed for some dose and suffer because of withdrawal. Therefore, it is quite logical that clients are severely depressed and it is very difficult for them to adapt physiologically a healthy lifestyle. Psychologically, during rehabilitation, clients understand why this is happening and realize their addiction as a disease, but their bodies are helpless, despite clients’ desire to get rid of the disease or to be cured. Based on the data analysis, we can see that the personal type of anxiety is characterized by deep depression according to the F-Fisher criterion (78.39), and the situational type of anxiety demonstrate easier signs of depression (51.92). We can argue for such findings by the fact that anxiety is always present in the personality type, but anxiety of the situational type depends on activities and lifestyle. In order to ease depressed states of the clients with chemical addictions, we used body-oriented therapy in practice. The performed formative experiment with proposed psychotherapy showed that clients’ depressive states significantly improved, they showed medium and low-medium levels of depression after the influence. That is, social psychological training through body-oriented therapy helped reduce depressive states.